Mythical Ages and Methodological Strictures - Joan Robinson's Contributions to the Theory of Economic Growth - Peter Skott (University of Massachusetts, Department of Economics, 2004)
This paper considers some methodological aspects of Joan Robinson's contribution to post-Keynesian growth theory. Joan Robinson's criticisms of equilibrium analysis, of the conflation of logical and historical time and of the uses (and misuses) of mathematical formalisation are scathing. But while many of her points are well taken, parts of her argument appear questionable. As a result, her methodological critique of equilibrium economics may be misleading. Moreover, she failed to appreciate the potential gains from mathematical formalisation. The further development of a Robinsonian analysis of economic growth calls for a reconsideration of these aspects of her legacy.
Keywords: B31; B41; O41; 330; Joan Robinson; equilibrium; stability; historical time